Epidemiology of MRI-detected muscle injury in athletes participating in the Tokyo 2020 Olympic Games - Katagiri, H.; Forster, B. B.; Engebretsen, L.; An, J.-S.; Adachi, T.; Saida, Y.; Onishi, K.; Koga, H. (British Journal of Sports Medicine, 2023)
Objective: Muscle injury is one of the most common injuries occurring at the Olympic Games often with devastating consequences. Epidemiological injury surveillance is recognised by the IOC as essential for injury prevention and management. We aimed to describe the incidence, anatomical location and classification of MRI-detected muscle injuries in athletes who participated in the Tokyo 2020 Olympic Games.